Exploring the Dynamics of University Systems: Navigating Structures, Challenges, and Innovations in Higher Education - Utami, Alma Yulia; Wahyuni, Ayu; Azaria, Liza (Pusat Studi Pembangunan dan Pemberdayaan, 2023)
This study delves into the dynamics of college systems, focusing on the relationship between organizational support and faculty job satisfaction in higher education. By utilizing a combination of quantitative analyses such as regression, ANCOVA, and Pearson correlation, along with qualitative insights, the study delves into the complex nature of higher education dynamics. The study shows a strong positive relationship between school perceptions of organizational support and levels of job satisfaction, highlighting the crucial role of supportive work environments in promoting employee well-being. Furthermore, the analysis emphasizes the significance of tackling issues such as financial limitations and changes in population demographics while adopting creative approaches to teaching and research.